"SPORTS ARE FUN": A Guide for the Discussion of Sport-Related Films. (July 2019) - Olympia, Robert P.; Lucas, Christy; Doraiswamy, Vignesh; Funghi, Cristina; Wakefield, Hannah M.; Wakefield, Bryan H.; Brady, Jodi
Sport participation is an important part of the development of children and adolescents in the United States. Due to the popularity of sport-related films, coaches, athletic trainers, and parents have used these films to both educate and motivate pediatric athletes. The objective of this study was to develop a discussion guide template based on common positive and negative themes depicted in sport-related films, and demonstrate the application of this discussion guide template to a select number of sport-related films released from 2014 to 2018. A discussion guide template ("SPORTS ARE FUN") was developed by the co-investigators, reflecting common themes of " S portsmanship, P articipation for All, O bstacles, R elationships, T eamwork, S etting Realistic Goals, A cademics, R esponsibility, E xercise/Nutrition/Rest/Drugs/Performance Enhancing Drugs, F un, U nrelenting Spirit, and " N o Pain, No Gain." The authors hope that pediatric health care providers, athletic coaches/staff, and parents can utilize this discussion guide template in the education and development of children and adolescents who participate in sports.